Basaloid squamous cell carcinoma of anal canal with adenoid cystic pattern and liver metastasis: A rare case report. Issue 5 (21st December 2021) - Rani, Usha; Tanwar, Parul; Jain, Shyam Lata; Verma, Nidhi; Dahiya, Sakshi; Lal, Pawanindra
Abstract: Anal malignancies are rare, and of these squamous cell carcinoma and basaloid squamous cell carcinoma are the most common types. Anal basaloid squamous carcinoma (BSC) can show a variety of patterns including unusual variants with cribriform areas resembling adenoid cystic carcinoma (ACC). BSC is reported more frequently in elderly females. Although the histopathology of BSC is characteristic, its cytomorphology is rarely described in the anorectal region. Due to overlapping morphological features, it is challenging to distinguish between ACC and BSC. Immunohistochemistry (IHC) is mandatory for this distinction and definite diagnosis, as it is a highly aggressive tumor with a tendency for distant metastasis. An interesting and rare case of BSC with ACC‐pattern arising in the anal canal with liver metastasis in a middle‐aged male is reported here. The aim is to highlight its cytological features, correlation with histology, IHC and its differential diagnoses.